Language testing in colombia: a call for more teacher education and teacher training in language assessment (2009)
Classroom assessment is an integral part of the language learning process and a powerful informed decision-making tool. Unfortunately, not many language teachers in Colombia are trained to make assessment decisions that will engage and motivate students and, as a result, enhance learning. In this article, we present the results of a study that examines teachers’ perceptions about language assessment and the way they use language assessments in their classroom. The findings suggest that there is a significant difference in the perceptions that teachers have depending on the level of training they have in language assessment. Thus, we highlight the importance of providing adequate training in language assessment for all prospective language teachers in Colombia. Key words: Teachers’ perceptions about classroom assessment, assessment use, assessment training La evaluación en el aula es parte integral del proceso de aprendizaje de una lengua extranjera y una herramienta poderosa para la toma de decisiones informadas. Infortunadamente, no muchos profesores de lenguas en Colombia tienen formación para tomar decisiones que permitan que el estudiante participe y esté motivado y, como resultado, promuevan el aprendizaje. En este artículo presentamos los resultados de un estudio que examina las percepciones de los profesores de lenguas sobre la evaluación y la forma en que la usan en el aula. Los resultados sugieren que existe una diferencia significativa en la percepción que tienen los profesores, dependiendo del nivel de formación que tienen en evaluación en lenguas. Por lo tanto, resaltamos la importancia de formar adecuadamente en evaluación a los futuros profesores de lenguas extranjeras en Colombia. Palabras clave: Percepciones de los docentes sobre la evaluación en el aula, uso de evaluaciones,formación en evaluación